Electrostatic self-assembly heterostructure neodymium-iron-boron magnet and preparation method thereof

CN122968083APending Publication Date: 2026-10-23INST OF RESOURCES UTILIZATION & RARE EARTH DEV GUANGDONG ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611094902.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明解决了现有钕铁硼磁体难以兼顾高电阻率和高热导率以及惰性绝缘材料在磁粉表面的均匀包覆与界面结合问题的问题,本发明的目的是提供一种静电自组装异质结构钕铁硼磁体及其制备方法,本发明通过微观结构设计,在钕铁硼磁粉表面构建具有绝缘和导热双功能的二维材料异质结包覆层,以制备低涡流损耗、高热稳定性的钕铁硼磁体

Benefits of technology

[0031]第一,本发明提出的异质结构钕铁硼磁体电阻率提升显著且均匀。通过静电自组装实现的六方氮化硼纳米片包覆层厚度可控,且覆盖率高,有效切断了晶粒间的导电通路,电阻率较未处理磁体显著提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968083A_ABST
    Figure CN122968083A_ABST
Patent Text Reader

Abstract

The application discloses a static self-assembly heterostructure neodymium-iron-boron magnet and a preparation method thereof. The static self-assembly heterostructure neodymium-iron-boron magnet has a core-shell structure and comprises a neodymium-iron-boron particle matrix core and a composite insulating layer coated on the surface of the matrix core. The composite insulating layer comprises a carbon-based intermediate layer and a hexagonal boron nitride insulating layer from inside to outside in sequence. The carbon-based intermediate layer is closely combined with the surface of the neodymium-iron-boron particle matrix core, and the boron nitride insulating layer is arranged on the surface of the carbon-based intermediate layer through electrostatic attraction. The thickness of the hexagonal boron nitride nanosheet coating layer realized through static self-assembly is controllable, the coverage is high, the conduction path between the crystal grains is effectively cut off, and the resistivity is significantly improved compared with that of the untreated magnet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rare earth permanent magnet materials technology, and in particular to an electrostatically self-assembled heterostructure neodymium iron boron magnet and its preparation method. Background Technology

[0002] As new energy vehicle drive motors develop towards higher speeds and higher power densities, neodymium iron boron (NdFeB) permanent magnets in the motor rotors face severe challenges in terms of eddy current losses and temperature-induced demagnetization. In recent years, reducing eddy current losses under variable frequency operation by increasing the resistivity of NdFeB magnets has become a common practice in the industry. Existing methods for increasing the resistivity of NdFeB magnets mainly involve coating the magnetic powder surface with SiO2, Al2O3, phosphates, or organic resins. While these materials have good insulation properties, they have extremely low thermal conductivity. This makes it difficult for heat generated inside the magnet to be conducted to the surface, creating a "heat accumulation effect" and leading to localized high-temperature demagnetization. Therefore, simply increasing the resistivity of NdFeB magnets while neglecting their heat dissipation efficiency presents a technical contradiction.

[0003] Hexagonal boron nitride (h-BN) possesses excellent insulation and extremely high in-plane thermal conductivity, making it an ideal coating material. However, h-BN has a highly chemically inert surface and lacks active functional groups. When directly mixed with NdFeB powder, the interfacial bonding is extremely poor, leading to easy detachment or agglomeration during sintering or hot pressing and deformation, resulting in decreased density. Traditional mechanical ball milling mixing methods struggle to form a uniform, continuous, and ultrathin coating layer on the surface of micron-sized magnetic powders. An excessively thick coating layer significantly reduces the volume fraction of the magnetic phase in the magnet, causing a severe magnetic dilution effect and weakening remanence. Summary of the Invention

[0004] This invention solves the problem that existing NdFeB magnets cannot simultaneously achieve high resistivity and high thermal conductivity, as well as the uniform coating and interfacial bonding of inert insulating materials on the surface of magnetic powder. The purpose of this invention is to provide an electrostatically self-assembled heterostructure NdFeB magnet and its preparation method. Through microstructure design, this invention constructs a two-dimensional material heterojunction coating layer with dual functions of insulation and thermal conductivity on the surface of NdFeB magnetic powder to prepare NdFeB magnets with low eddy current loss and high thermal stability.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is: an electrostatically self-assembled heterostructure neodymium iron boron magnet, wherein the neodymium iron boron magnet has a core-shell structure, including a neodymium iron boron particle matrix core and a composite insulating layer covering the surface of the matrix core; the composite insulating layer includes a carbon-based intermediate layer and a hexagonal boron nitride insulating layer from the inside out, the carbon-based intermediate layer is closely attached to the surface of the neodymium iron boron particle matrix core, and the boron nitride insulating layer is disposed on the surface of the carbon-based intermediate layer by electrostatic attraction.

[0006] This invention utilizes electrostatic self-assembly technology to construct a multilayer heterogeneous structure on the surface of neodymium iron boron magnetic powder. Specifically, the structure consists of three layers from the inside out: the innermost layer is the neodymium iron boron magnetic powder core layer, the middle layer is reduced graphene oxide (i.e., carbon-based intermediate layer), and the outermost layer is an inert insulating material (hexagonal boron nitride insulating layer).

[0007] This invention also protects the method for preparing the above-mentioned electrostatically self-assembled heterostructure NdFeB magnet, comprising the following steps:

[0008] (1) Add neodymium iron boron magnetic powder to polyethyleneimine (PEI) ethanol solution and disperse it so that polyethyleneimine molecules are physically adsorbed and wrapped on the surface of neodymium iron boron magnetic powder. Filter to obtain modified neodymium iron boron magnetic powder with positive charge on the surface.

[0009] (2) Prepare a single-layer graphene oxide dispersion using a deionized water / ethanol mixture, and adjust the pH of the dispersion to 6.0~8.0 to ensure that the graphene oxide surface is negatively charged;

[0010] (3) Add the modified neodymium iron boron magnetic powder obtained in step (1) to the single-layer graphene oxide dispersion obtained in step (2) and stir evenly. Use electrostatic attraction to adsorb and form graphene oxide coating. Filter to obtain composite magnetic powder with graphene oxide coating on the outer layer.

[0011] (4) Hexagonal boron nitride powder is exfoliated in isopropanol, the upper nanosheet suspension is centrifuged, and an aqueous solution of cationic surfactant is added to make the surface of hexagonal boron nitride positively charged to obtain hexagonal boron nitride suspension.

[0012] (5) After adding the composite magnetic powder obtained in step (3) to the hexagonal boron nitride suspension and stirring evenly, the positively charged hexagonal boron nitride nanosheets are oriented and anchored on the surface of the negatively charged graphene oxide layer to form a dense coating shell. Then, the mixture is filtered and vacuum dried to obtain composite neodymium iron boron magnetic powder with a multi-layer core-shell structure.

[0013] (6) Vacuum hot pressing of composite neodymium iron boron magnetic powder with multi-layer core-shell structure to obtain isotropic hot-pressed magnet;

[0014] (7) Under vacuum and high temperature conditions, axial pressure is applied to the upper and lower surfaces of the hot-pressed magnet to perform upsetting deformation until the height of the magnet is 20% to 40% of the original height of the magnet, thus obtaining an anisotropic magnet.

[0015] Preferably, the neodymium iron boron magnetic powder in step (1) is a fast-quenching magnetic powder with a nanocrystalline structure, and the particle size of the neodymium iron boron magnetic powder is <270 μm.

[0016] Preferably, the concentration of the polyethyleneimine ethanol solution in step (1) is 1.5~3.0 g / L, and the mass-to-volume ratio of neodymium iron boron magnetic powder to polyethyleneimine ethanol solution is 1 g: 0.8~1.2 mL.

[0017] Further preferred, the concentration of the polyethyleneimine ethanol solution in step (1) is 2.0 g / L, and the mass-to-volume ratio of neodymium iron boron magnetic powder to polyethyleneimine ethanol solution is 1 g: 1 mL.

[0018] Preferably, in step (2), the volume ratio of deionized water to ethanol in the deionized water / ethanol mixture is 0.8~1.2:1, and the concentration of the monolayer graphene oxide dispersion is 0.5~1.0 mg / mL. Ammonia is used to adjust the pH of the dispersion.

[0019] Further preferred, in step (2), the volume ratio of deionized water to ethanol in the deionized water / ethanol mixture is 1:1, and the concentration of the monolayer graphene oxide dispersion is 0.8 mg / mL.

[0020] Preferably, the mass-to-volume ratio of the modified NdFeB magnetic powder to the monolayer graphene oxide dispersion in step (3) is 1 g: 1~3 mL.

[0021] Further preferred, the mass-to-volume ratio of the modified NdFeB magnetic powder to the monolayer graphene oxide dispersion in step (3) is 1 g: 2 mL.

[0022] Preferably, the mass-to-volume ratio of hexagonal boron nitride powder to isopropanol in step (4) is 0.8~1.2 g:100mL, the mass ratio of hexagonal boron nitride to cationic surfactant is 100:1~3, and the concentration of the aqueous solution of cationic surfactant is 0.1~1 g / L.

[0023] Further preferably, the mass-to-volume ratio of hexagonal boron nitride powder to isopropanol in step (4) is 1 g:100 mL, the mass ratio of hexagonal boron nitride to cationic surfactant is 100:2, and the concentration of the aqueous solution of cationic surfactant is 0.5 g / L. The cationic surfactant is CTAB.

[0024] Preferably, the mass-to-volume ratio of the composite magnetic powder to the hexagonal boron nitride suspension in step (5) is 1 g: 80~120 mL.

[0025] Further preferred, the mass-to-volume ratio of the composite magnetic powder to the hexagonal boron nitride suspension in step (5) is 1 g: 100 mL.

[0026] Preferably, the vacuum hot pressing in step (6) adopts a two-stage heating process. The first stage is a low-temperature debinding stage, with a temperature of 300℃~400℃ and a holding time of 50~70 min. The second stage is a hot pressing densification stage, with a temperature of 650℃~750℃, a pressure of 180~220 MPa, and a holding time of 25~35 min.

[0027] Further preferred, the vacuum hot pressing in step (6) adopts a two-stage heating process. The first stage is a low-temperature debinding stage, with the temperature controlled at 300℃~400℃ and held for 60 min. The second stage is a hot pressing densification stage, with the temperature controlled at 700℃, the pressure at 200MPa, and held for 30 min.

[0028] Preferably, the deformation process temperature in step (7) is 650℃~750℃, with a time interval of 0.0005~0.0015 s. -1 The deformation rate continues until the magnet height is 20% to 40% of the original magnet height.

[0029] Further preferably, the deformation process temperature in step (7) is 700℃, with a time interval of 0.001 s. -1 The deformation rate continues until the magnet height is 30% of the original magnet height.

[0030] Compared with the prior art, the beneficial effects of the present invention are:

[0031] First, the heterostructured NdFeB magnet proposed in this invention exhibits a significant and uniform increase in resistivity. The hexagonal boron nitride nanosheet coating layer, achieved through electrostatic self-assembly, has a controllable thickness and high coverage, effectively severing the conductive pathways between grains, resulting in a significantly higher resistivity compared to the untreated magnet.

[0032] Second, this invention improves the thermal conductivity of the magnet. Compared to traditional oxide insulating layers, this invention utilizes the high intrinsic thermal conductivity of hexagonal boron nitride nanosheets and uses reduced graphene oxide to repair the interfacial lattice mismatch between the substrate and the insulating layer, reducing the interfacial thermal resistance, thus increasing the overall thermal conductivity of the magnet.

[0033] Third, the present invention introduces a small amount of non-magnetic phase, resulting in minimal loss of magnetic properties in the magnet. Unlike traditional powder mixing and addition, the present invention employs an electrostatic self-assembly method, resulting in a thin overall thickness of the non-magnetic coating layer on the surface of the magnetic powder, a low volume fraction of the non-magnetic phase, and a minimal dilution effect on the remanence of the magnet. Attached Figure Description

[0034] Figure 1 This is a polished SEM image of the cross-section of the anisotropic magnet prepared in Example 1.

[0035] Figure 2 This is a TEM image of the anisotropic magnet prepared in Example 1, perpendicular to the pressing direction.

[0036] Figure 3 This is a TEM image of the anisotropic magnet prepared in Example 1, parallel to the pressing direction. Detailed Implementation

[0037] The following embodiments are further illustrations of the present invention, but not limitations thereof. Unless otherwise specified, the equipment used in the present invention is a commercially available product conventional in this technical field.

[0038] An electrostatically self-assembled heterostructure neodymium iron boron magnet has a core-shell structure, comprising a neodymium iron boron particle matrix core and a composite insulating layer covering the surface of the matrix core. The composite insulating layer, from the inside out, comprises a carbon-based intermediate layer and a hexagonal boron nitride insulating layer. The carbon-based intermediate layer is tightly bonded to the surface of the neodymium iron boron particle matrix core, and the boron nitride insulating layer is attached to the surface of the carbon-based intermediate layer by electrostatic attraction. The carbon-based intermediate layer is reduced graphene oxide.

[0039] Example 1

[0040] The method for preparing electrostatically self-assembled heterostructure NdFeB magnets includes the following steps:

[0041] First, 100 g of commercially available NdFeB rapidly quenched magnetic powder with an average particle size of < 270 μm was added to 100 mL of anhydrous PEI ethanol solution with a concentration of 2.0 g / L. The powder was then ultrasonically dispersed at a frequency of 40 kHz for 15 min, allowing PEI molecules to uniformly coat the surface of the NdFeB magnetic powder through physical adsorption. After centrifugation, the powder was washed three times with anhydrous ethanol, filtered, and dried to obtain positively charged modified magnetic powder.

[0042] Next, a dispersion with a concentration of 0.8 mg / mL was prepared using monolayer graphene oxide with an average sheet diameter of 1.0 μm and 100 mL of deionized water / ethanol at a volume ratio of 1:1. The pH was adjusted to 7.5 with dilute ammonia to ensure that the carboxyl and hydroxyl groups on the surface of the graphene oxide were fully deprotonated, thus ensuring that its surface was negatively charged. The modified magnetic powder was slowly added to the dispersion at a mass-to-volume ratio of 1 g: 2 mL, and mechanically stirred at 300 r / min for 30 min to form a graphene oxide coating by electrostatic attraction. After filtration and washing, a composite modified magnetic powder with an outer layer of graphene oxide was obtained.

[0043] Then, hexagonal boron nitride (h-BN) powder with an average flake diameter of 0.5 μm was added to isopropanol at a ratio of 1 g:100 mL. Liquid-phase exfoliation was performed by ultrasonic exfoliation at 300 W for 5 h, followed by centrifugation at 300 r / min for 15 min. The supernatant was collected to obtain an h-BN nanosheet suspension. An aqueous solution of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) at a concentration of 0.5 g / L was added to this suspension, making the mass ratio of h-BN to CTAB 100:2. After stirring and mixing for 30 min, CTAB adsorbed onto the surface of the BN nanosheets, giving them a positive charge, resulting in a stable and dispersed h-BN nanosheet suspension.

[0044] Next, the composite modified magnetic powder was added to the h-BN suspension at a mass-to-volume ratio of 1 g:100 mL. The mixture was stirred at a low speed of 150 r / min for 30 min. This allowed the positively charged hexagonal boron nitride nanosheets to be oriented and anchored onto the surface of the negatively charged graphene oxide layer, forming a dense coating shell. After the reaction was complete, the mixture was filtered and vacuum dried at 80 °C to obtain composite NdFeB magnetic powder with a multi-layered core-shell structure.

[0045] Subsequently, the resulting modified composite magnetic powder was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for hot-pressing densification, with a vacuum degree of less than 1×10⁻⁶. -2 Pa. A two-stage heating process is adopted. The first stage is a low-temperature debinding stage, in which the temperature is controlled at 400℃ and held for 60 min. The second stage is a hot-pressing densification stage, in which the temperature is controlled at 700℃ and an axial pressure of 200 MPa is applied and held for 30 min, finally obtaining an isotropic hot-pressed magnet.

[0046] Finally, when the vacuum degree is less than 1×10 -2 Under Pa conditions, heating to 700℃ and applying pressure to a hot-pressed magnet at 0.001 s⁻¹ -1 The magnet is upsetting at a certain deformation rate until the height of the magnet is 30% of the original height, thus obtaining an anisotropic magnet.

[0047] The obtained anisotropic magnets were characterized as follows: Figure 1-3 As shown, Figure 1 This is a fracture morphology diagram of the magnet, showing the typical lamellar crystal structure of a thermally deformed Nd-Fe-B magnet. The grains exhibit a clear orientational alignment along the pressing direction, indicating that the magnet has achieved a high degree of texture. Figure 2 and Figure 3 These are TEM images showing the magnet parallel and perpendicular to the pressing direction, respectively.

[0048] Comparative Example 1

[0049] First, 100 g of commercial NdFeB rapidly quenched magnetic powder with an average particle size of < 270 μm was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for hot pressing densification, with a vacuum degree of less than 1×10⁻⁶. -2 Pa. A two-stage heating process was adopted. In the first stage, the temperature was controlled at 400℃ and held for 60 min. In the second stage, the temperature was controlled at 700℃ and axial pressure of 200 MPa was applied and held for 30 min to finally obtain an isotropic hot-pressed magnet.

[0050] Finally, when the vacuum degree is less than 1×10 -2 Under Pa conditions, heating to 700℃ and applying pressure to a hot-pressed magnet at 0.001 s⁻¹ -1 The magnet is upsetting at a certain deformation rate until the height of the magnet is 30% of the original height, thus obtaining an anisotropic magnet.

[0051] Comparative Example 2

[0052] First, 100 g of commercially available NdFeB rapidly quenched magnetic powder with an average particle size of < 270 μm was added to 100 mL of anhydrous PEI ethanol solution with a concentration of 2.0 g / L. The powder was then ultrasonically dispersed at a frequency of 40 kHz for 15 min, allowing PEI molecules to uniformly coat the surface of the NdFeB magnetic powder through physical adsorption. After centrifugation, the powder was washed three times with anhydrous ethanol, filtered, and dried to obtain positively charged modified magnetic powder.

[0053] Next, a dispersion with a concentration of 0.8 mg / mL was prepared using monolayer graphene oxide with an average sheet diameter of 1.0 μm and 100 mL of deionized water / ethanol at a volume ratio of 1:1. The pH was adjusted to 7.5 with dilute ammonia to ensure that the carboxyl and hydroxyl groups on the surface of the graphene oxide were fully deprotonated, thus ensuring that its surface was negatively charged. The modified magnetic powder was slowly added to the dispersion at a mass-to-volume ratio of 1 g: 2 mL, and mechanically stirred at 300 r / min for 30 min to form a graphene oxide coating by electrostatic attraction. After filtration and washing, a composite modified magnetic powder with an outer layer of graphene oxide was obtained.

[0054] Subsequently, the composite modified magnetic powder with an outer layer of graphene oxide was loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for hot pressing densification, with a vacuum degree of less than 1×10⁻⁶. -2 Pa. A two-stage heating process is adopted. The first stage is a low-temperature debinding stage, in which the temperature is controlled at 400℃ and held for 60 min. The second stage is a hot-pressing densification stage, in which the temperature is controlled at 700℃ and an axial pressure of 200 MPa is applied and held for 30 min, finally obtaining an isotropic hot-pressed magnet.

[0055] Finally, when the vacuum degree is less than 1×10 -2Under Pa conditions, heating to 700℃ and applying pressure to a hot-pressed magnet at 0.001 s⁻¹ -1 The magnet is upsetting at a certain deformation rate until the height of the magnet is 30% of the original height, thus obtaining an anisotropic magnet.

[0056] Comparative Example 3

[0057] First, 100 g of commercially available NdFeB rapidly quenched magnetic powder with an average particle size of < 270 μm was added to 100 mL of anhydrous PEI ethanol solution with a concentration of 2.0 g / L. The powder was then ultrasonically dispersed at a frequency of 40 kHz for 15 min, allowing PEI molecules to uniformly coat the surface of the NdFeB magnetic powder through physical adsorption. After centrifugation, the powder was washed three times with anhydrous ethanol, filtered, and dried to obtain positively charged modified magnetic powder.

[0058] Next, hexagonal boron nitride (h-BN) powder with an average flake diameter of 0.5 μm was added to isopropanol at a ratio of 1 g:100 mL. Liquid-phase exfoliation was performed by ultrasonic exfoliation at 300 W for 5 h, followed by centrifugation at 300 r / min for 15 min. The supernatant was collected to obtain an h-BN nanosheet suspension. An aqueous solution of the cationic surfactant cetyltrimethylammonium bromide (CTAB) at a concentration of 0.5 g / L was added to this suspension, making the mass ratio of h-BN to CTAB 100:2. After stirring and mixing for 30 min, CTAB adsorbed onto the surface of the BN nanosheets, giving them a positive charge, resulting in a stable and dispersed h-BN nanosheet suspension.

[0059] Next, the modified magnetic powder was added to the h-BN suspension at a mass-to-volume ratio of 1 g:100 mL. The mixture was stirred at a low speed of 150 r / min for 30 min. Due to the absence of a graphene oxide interlayer, the h-BN nanosheets adhered to the magnetic powder surface primarily through mechanical contact and van der Waals forces, forming a discontinuous hexagonal boron nitride coating. After the reaction was complete, the mixture was filtered and vacuum dried at 80 °C to obtain the composite NdFeB magnetic powder.

[0060] Subsequently, the obtained magnetic powder is loaded into a graphite mold and placed in a vacuum hot-pressing sintering furnace for hot pressing and densification, with a vacuum degree of less than 1×10⁻⁶. -2 Pa. A two-stage heating process is adopted. The first stage is a low-temperature debinding stage, in which the temperature is controlled at 400℃ and held for 60 min. The second stage is a hot-pressing densification stage, in which the temperature is controlled at 700℃ and an axial pressure of 200 MPa is applied and held for 30 min, finally obtaining an isotropic hot-pressed magnet.

[0061] Finally, when the vacuum degree is less than 1×10 -2 Under Pa conditions, heating to 700℃ and applying pressure to a hot-pressed magnet at 0.001 s⁻¹ -1The magnet is upsetting at a certain deformation rate until the height of the magnet is 30% of the original height, thus obtaining an anisotropic magnet.

[0062] The magnet samples were machined to suitable dimensions for performance testing. The resistivity of the magnets was measured using the four-probe method; the thermal conductivity was measured using the laser scintillation method; and the remanence and coercivity were measured using a pulsed magnetic field magnetometer. The test direction was parallel to the axial pressure direction, i.e., the magnetic easy axis direction. The room temperature performance of the magnets obtained in Example 1 and Comparative Examples 1, 2, and 3 is shown in Table 1.

[0063] Table 1. Magnetic properties of the magnets obtained in Example 1 and Comparative Examples 1-3, parallel to the pressure direction at room temperature.

[0064] As shown in Table 1, compared with magnets coated with reduced graphene oxide alone (Comparative Example 2), this invention introduces hexagonal boron nitride nanosheets with high intrinsic thermal conductivity, and utilizes reduced graphene oxide to construct a flexible transition interface between the NdFeB matrix and the hexagonal boron nitride insulating layer, improving the interface contact state, promoting heat transfer, thereby reducing the interface thermal resistance, and enabling the magnet to obtain higher thermal conductivity while maintaining excellent insulation performance.

[0065] Furthermore, compared to Comparative Example 2, which is coated with reduced graphene oxide alone, and Comparative Example 3, which is coated with hexagonal boron nitride alone, the present invention constructs a continuous and uniform heterogeneous coating structure through electrostatic self-assembly. This structure can more effectively block the electron transport path between grains, while ensuring the uniform distribution and complete coverage of the insulating layer on the surface of the magnetic powder. Therefore, the resistivity of the magnet is significantly higher than that of Comparative Examples 1-3.

[0066] Example 2

[0067] Same as Example 1, except that:

[0068] The concentration of the polyethyleneimine ethanol solution was 1.5 g / L, and the mass-to-volume ratio of NdFeB magnetic powder to the polyethyleneimine ethanol solution was 1 g:1.2 mL; the volume ratio of deionized water to ethanol in the deionized water / ethanol mixture was 0.8:1, and the concentration of the monolayer graphene oxide dispersion was 0.5 mg / mL; the mass-to-volume ratio of modified NdFeB magnetic powder to the monolayer graphene oxide dispersion was 1 g:1 mL.

[0069] Example 3

[0070] Same as Example 1, except that:

[0071] The concentration of the polyethyleneimine ethanol solution was 3.0 g / L, and the mass-to-volume ratio of NdFeB magnetic powder to the polyethyleneimine ethanol solution was 1 g:0.8 mL; the volume ratio of deionized water to ethanol in the deionized water / ethanol mixture was 1.2:1, the concentration of the monolayer graphene oxide dispersion was 1.0 mg / mL, and the mass-to-volume ratio of modified NdFeB magnetic powder to the monolayer graphene oxide dispersion was 1 g:3 mL.

[0072] Example 4

[0073] Same as Example 1, except that:

[0074] The mass-to-volume ratio of hexagonal boron nitride powder to isopropanol was 0.8 g:100 mL, the mass ratio of hexagonal boron nitride to CTAB was 100:1, and the concentration of the CTAB aqueous solution was 0.4 g / L; the mass-to-volume ratio of composite magnetic powder to hexagonal boron nitride suspension was 1 g:80 mL; the vacuum hot pressing process employed a two-stage heating process: the first stage was a low-temperature debinding stage, controlled at 300℃ and held for 70 min; the second stage was a hot pressing densification stage, controlled at 650℃ and 180 MPa, held for 35 min; the deformation process temperature was 650℃, with a pressing speed of 0.0005 s⁻¹. -1 The deformation rate continues until the magnet height is 20% of the original magnet height.

[0075] Example 5

[0076] Same as Example 1, except that:

[0077] The mass-to-volume ratio of hexagonal boron nitride powder to isopropanol was 1.2 g:100 mL, the mass ratio of hexagonal boron nitride to CTAB was 100:3, and the concentration of the CTAB aqueous solution was 0.6 g / L; the mass-to-volume ratio of composite magnetic powder to hexagonal boron nitride suspension was 1 g:120 mL; the vacuum hot pressing process employed a two-stage heating process: the first stage was a low-temperature debinding stage, controlled at 400℃ and held for 50 min; the second stage was a hot pressing densification stage, controlled at 750℃ and 220 MPa, held for 25 min; the deformation process temperature was 750℃, with a pressing speed of 0.0015 s⁻¹. -1 The deformation rate continues until the magnet height is 40% of the original magnet height.

[0078] Table 2 Magnetic properties of magnets in Examples 2-5 at room temperature parallel to the pressure direction

[0079] The above are merely preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be considered as limitations on the present invention, and the scope of protection of the present invention should be determined by the scope defined in the claims. For those skilled in the art, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A neodymium iron boron magnet with an electrostatic self-assembled heterostructure, characterized in that: The neodymium iron boron magnet has a core-shell structure, including a neodymium iron boron particle matrix core and a composite insulating layer covering the surface of the matrix core; the composite insulating layer includes a carbon-based intermediate layer and a hexagonal boron nitride insulating layer from the inside to the outside, the carbon-based intermediate layer is closely attached to the surface of the neodymium iron boron particle matrix core, and the boron nitride insulating layer is set on the surface of the carbon-based intermediate layer by electrostatic attraction.

2. The method for preparing the electrostatically self-assembled heterostructure NdFeB magnet according to claim 1, characterized in that, Includes the following steps: (1) Add neodymium iron boron magnetic powder to polyethyleneimine ethanol solution and disperse it so that polyethyleneimine molecules are physically adsorbed and wrapped on the surface of neodymium iron boron magnetic powder. Filter to obtain modified neodymium iron boron magnetic powder with positive charge on the surface. (2) Prepare a single-layer graphene oxide dispersion using a deionized water / ethanol mixture, and adjust the pH of the dispersion to 6.0~8.0 to ensure that the graphene oxide surface is negatively charged; (3) Add the modified neodymium iron boron magnetic powder obtained in step (1) to the single-layer graphene oxide dispersion obtained in step (2) and stir evenly. Use electrostatic attraction to adsorb and form graphene oxide coating. Filter to obtain composite magnetic powder with graphene oxide coating on the outer layer. (4) Hexagonal boron nitride powder is exfoliated in isopropanol, the upper nanosheet suspension is centrifuged, and an aqueous solution of cationic surfactant is added to make the surface of hexagonal boron nitride positively charged to obtain hexagonal boron nitride suspension. (5) After adding the composite magnetic powder obtained in step (3) to the hexagonal boron nitride suspension and stirring evenly, the positively charged hexagonal boron nitride nanosheets are oriented and anchored on the surface of the negatively charged graphene oxide layer to form a dense coating shell. Then, the mixture is filtered and vacuum dried to obtain composite neodymium iron boron magnetic powder with a multi-layer core-shell structure. (6) Vacuum hot pressing of composite neodymium iron boron magnetic powder with multi-layer core-shell structure to obtain isotropic hot-pressed magnet; (7) Under vacuum and high temperature conditions, axial pressure is applied to the upper and lower surfaces of the hot-pressed magnet to perform upsetting deformation until the height of the magnet is 20% to 40% of the original height of the magnet, thus obtaining an anisotropic magnet.

3. The preparation method according to claim 2, characterized in that, The neodymium iron boron magnetic powder mentioned in step (1) is a fast-quenching magnetic powder with a nanocrystalline structure and a particle size of <270 μm.

4. The preparation method according to claim 2 or 3, characterized in that, The concentration of the polyethyleneimine ethanol solution in step (1) is 1.5~3.0 g / L, and the mass-volume ratio of neodymium iron boron magnetic powder to polyethyleneimine ethanol solution is 1 g: 0.8~1.2 mL.

5. The preparation method according to claim 2, characterized in that, In step (2), the volume ratio of deionized water to ethanol in the deionized water / ethanol mixture is 0.8~1.2:1, and the concentration of the monolayer graphene oxide dispersion is 0.5~1.0 mg / mL.

6. The preparation method according to claim 2, characterized in that, The mass-to-volume ratio of the modified NdFeB magnetic powder to the monolayer graphene oxide dispersion in step (3) is 1 g: 1~3 mL.

7. The preparation method according to claim 2, characterized in that, The mass-to-volume ratio of hexagonal boron nitride powder to isopropanol in step (4) is 0.8~1.2 g:100 mL, the mass ratio of hexagonal boron nitride to cationic surfactant is 100:1~3, and the concentration of the aqueous solution of cationic surfactant is 0.4~0.6 g / L.

8. The preparation method according to claim 2, characterized in that, The mass-to-volume ratio of the composite magnetic powder to the hexagonal boron nitride suspension in step (5) is 1 g: 80~120 mL.

9. The preparation method according to claim 2, characterized in that, The vacuum hot pressing in step (6) adopts a two-stage heating process. The first stage is the low-temperature debinding stage, with the temperature controlled at 300℃~400℃ and held for 50~70 min. The second stage is the hot pressing densification stage, with the temperature controlled at 650℃~750℃, the pressure at 180~220 MPa, and held for 25~35 min.

10. The preparation method according to claim 2, characterized in that, The deformation process in step (7) is carried out at a temperature of 650℃~750℃, with a time interval of 0.0005~0.0015 s. -1 The deformation rate continues until the magnet height is 20% to 40% of the original magnet height.